Synthesis of Transition Metal-Nanochitosan Composites Using Ni, Cu, Zn, and Ag Metal Ions and Applications as Antibacterial Agents - Khoirina Dwi Nugrahaningtyas; Eny Kusrini; Salwa Salsabila; Dina Fitriana; Anwar Usman; Triana Kusumaningsih; Sri Juari Santoso (International Journal of Technology)
Nanocomposites are used as antibacterial agents in the pharmacology sector. Therefore, this research aimed to investigate the synthesis, characterization, and antibacterial activity of the transition metal-nanochitosan composites (TM-NCs) using Ni (nickel), Cu (cuprum), Zn (zinc), and Ag (silver) as TM and nanochitosan as the nanomaterial. TM-NCs were synthesized using precipitation method with sodium tripolyphosphate (STPP) as a cross-linking agent. The synthesized products were characterized using X-ray Fluorescence (XRF), X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), and Scanning Electron Microscopy (SEM) instruments. The metal phase attached to NCs was a metal oxide with irregular particle shapes and various particle sizes. Meanwhile, chitosan and STPP functional groups, namely NH2 and P-O were bound to the metal to form TM-NCs nanocomposite. The test for antibacterial activity against gram-positive (Streptococcus pyogenes ATCC 19615 and Bacillus cereus ATCC 10556) and gram-negative (Escherichia coli ATCC 11229 and Klebsiella pneumoniae ATCC 13883) bacterial strains was carried out using the well-diffusion method. The results showed that Ni-NCs antibacterial activity had the largest inhibition zone compared to the other TM-NCs. Furthermore, Ni-NCs presented the largest inhibitory zone diameter (21.74 mm) towards the gram-positive bacterium S. pyogenes.